The cardiac jelly extracellular matrix contributes to valve development and overall cardiac function - Ostwald, Paige, author; Garrity, Deborah, advisor; Bark, David, committee member; Bedinger, Patricia, committee member; Nishimura, Erin, committee member; Peers, Graham, committee member (Colorado State University. Libraries, 2022)
Nearly 2.6 million infants are born every year with a congenital cardiac anomaly across the entire globe. Congenital heart defects (CHDs) within the valve occur in over 50% of cases. 56% of heart defects have an unknown etiology, illuminating the need for continuous research on heart development and potential causes. Before the valve is a mature structure with established leaflets, the heart forms two endocardial cushions that press together to occlude blood flow between chambers. The cushions are composed of an extracellular matrix called the cardiac jelly (CJ). Previous studies have found evidence of the vital role the cardiac jelly plays within the developing valve for structure, genetic signaling and cell organization. Here, we present a specific role the cardiac jelly plays in valve function and overall cardiac output. To alter the cardiac jelly, we used a morpholino approach in a zebrafish model to increase, decrease and structurally compromise the cardiac jelly. By doing so, we found decreased valve cell differentiation with decreased CJ and increased valve cell differentiation with increased CJ. Using high-speed video technology, we also found decreased valve opening regardless of cardiac jelly alteration, resulting in reduced overall cardiac function. Our results suggest that the function of the endocardial cushions relies on an appropriate presence of CJ. We next investigated just how the cardiac jelly may be altered during development. To do so, we exposed zebrafish embryos to hyperglycemic conditions during the initial and critical heart development period. We found that when embryos absorb over 1.5-fold more D-glucose due to high-glucose conditions, they exhibit significant alterations to CJ width. Altered CJ due to hyperglycemic conditions affected valve differentiation, valve opening, and cardiac function, particularly when embryos have absorbed over a 2-fold increase of glucose. Together, these results show the structural role of the cardiac jelly to support endocardial cushion opening which will supply enough oxygenated blood to the embryo.
Keywords: heart development; valve development; cardiac jelly; zebrafish; maternal diabetes